Are employability and entrepreneurial measures for higher education relevant? Introducing AGILE reflection. Issue 6 (December 2018) - Clinkard, Karen
This article considers the relevance of current measures of employability and entrepreneurial (E&E) outcomes for evaluating the longer term value of a course of higher education (HE) study. HE stakeholders continue to discuss whether exit performance metrics engender positive or negative responses, with educators arguing that E&E outcomes should not focus heavily on hard skills, but should take into account a broader range of behavioural, attitudinal and mindset changes, claiming that these provide greater longitudinal value for graduates. Through a critical review of literature and models, the article explores the effectiveness of HE first-destination metrics in capturing E&E outcomes; whether explicit links exist between the metrics and outcomes; and what role students have in developing a narrative of their own E&E outcomes. The discussion examines 'atheoretical' perspectives in E&E education and issues of generalizability due to contextual variability, but identifies common key mindset dimensions that are incorporated into a proposed 'AGILE' learning tool so that students can reflect and develop a narrative of their E&E-related development against: adaptable, gatherer, identity awareness, life-long learning and enterprising capabilities. Thus, it sets out an approach that HE stakeholders may wish to consider embedding in their own curricula, which places the onus on students to reflect, self-evaluate and record personalized 'small wins'.